A Control for an Unbalanced 3-Phase Load in UPS Systems - Rymarski, Zbigniew; Bernacki, Krzysztof; Dyga, Lukasz (Elektronika ir Elektrotechnika, 2018)
Single input single output systems (SISO), which only control the output voltage of a voltage source inverter (VSI) using multi-loop feedback, are not sufficient in the event of a 3-phase unbalanced load. A much better solution is a Multi Input Single Output (MISO) control. In such a case, not only is the output voltage controlled but also the output current and the output filter inductor current. It seems that using a Passivity Based Control (PBC) is just one of the better solutions for a VSI. The paper presents simulations of a modified Improved PBC (IPBC2) using a stationary αβ frame in the event of an unbalanced load in a 3-wire delta load. The simulations were verified using the measurements of a 3-phase inverter experimental model with dynamic balanced and unbalanced loads. DOI: http://dx.doi.org/10.5755/j01.eie.24.4.21474